Possibilities and limits of public intervention aimed at LGTB+ people in Chile - Galaz Valderrama, Caterine; Troncoso Pérez, Lelya (Critical Proposals in Social Work, 2021)
In recent years the demands of LGTB + groups in Chile have intensified and the State has been responding reactively with some policies and public interventions, but from logics that continue to be binary and hetero-cis-normative. From a critical view of public policies, we problematize how they establish a previous subject of intervention from an identity perspective. Results of a qualitative research based on interviews with professionals from various public services and LGTB + people who use these services in three urban centers in Chile: Santiago, Concepción and Valparaíso, are presented. Among the main results are the conceptions about "sexual diversity" in direct intervention with these groups; the possibilities and limits that have been articulated in the areas of health and education, considering them as two relevant areas in the intervention, together with the openings that have been given in local governments on the subject. It is concluded that an ideal of “diversity” has been extended within the intervention that can conceal new inequalities and reify new positions of subordination of non-normative sexualities.